Foundations of idiographic methods in psychology and applications for psychotherapy - Piccirillo, Marilyn L.; Rodebaugh, Thomas L. (Clinical psychology review, 2019)
Researchers have long called for greater recognition and use of longitudinal, individual-level research in the study of psychopathology and psychotherapy. Much of our current research attempts to indirectly investigate individual-level, or idiographic, psychological processes via group-based, or nomothetic, designs. However, results from nomothetic research do not necessarily translate to the individual-level. In this review, we discuss how idiographic analyses can be integrated into psychotherapy and psychotherapy research. We examine and review key statistical methods for conducting idiographic analyses. These methods include factor-based and vector autoregressive approaches using longitudinal data. The theoretical framework behind each approach is reviewed and critically evaluated. Empirical examples of each approach are discussed, with the aim of helping interested readers consider how they may use idiographic methods to analyze longitudinal data and psychological processes. Finally, we conclude by citing key limitations of the idiographic approach, calling for greater development of these analyses to ease their successful integration into clinical settings. •Researchers have called for greater use of longitudinal, idiographic designs•Idiographic methods show promise for personalizing assessment and therapy•We review key methods to assist researchers in conducting idiographic research•Limitations of integrating idiographic approaches into clinical work are discussed